Civilian peacekeeping: a barely tapped ressource - Institut für Friedensarbeit und Gewaltfreie Konfliktaustragung e.V (2010)
Abstract: Christine Schweitzer: Introduction - Civilian peacekeeping. A barely tapped ressource (7-16); Rolf Carrière: The world needs 'another peacekeeping' (17-24); Tim Wallis: Best practices for unarmed civilian peacekeeping (25-34); Rachel Julians: Peacekeeping with nonviolence: protection strategies for sustainable peace (35-42); Christine Schweitzer: Humanitarian protection as an additional function of humanitarian, development and peace projects - or rather a task requiring experts? (43-52); Christine Schweitzer: The responsibility to protect: towards an expanded role for global civil society (53-64)